EMPOWERING STUDENT CRITICAL THINKING SKILLS: HOW GUIDED INQUIRY ENHANCES CRITICAL SKILLS IN ECONOMICS - Azmi, Radeya Haris Ulul; Kurniawan, Riza Yonisa (JURNAL EDUSCIENCE, 2025)
Purpose- Critical Thinking is an important skill that students must possess in understanding and applying the concept of Basic Accounting in Economic Subjects. Many students have difficulty analyzing financial transactions and compiling accounting reports. This study aims to analyze students' critical thinking skills in economics subjects of basic accounting materials. The learning process employs a guided inquiry model.Methodology- The study involved 32 senior high school students in Sidoarjo Regency. This research utilizes a quantitative descriptive method structured with a one-group pre-test-post-test design. Data collection was conducted through observation and testing, using observation sheets to assess the implementation of the learning model and question sheets to evaluate critical thinking skills. Quantitative analysis with statistical tests was employed to analyze the data.Findings- The findings revealed an improvement in students' critical thinking skills, as reflected in the n-gain score, particularly for the interpretation indicator, which achieved a value of 0.78, inference worth 0.77, analysis value of 0.64, and explanatory worth 0.85. These four indicators fall into the high category. The paired sample t-test results showed a significance value (2-tailed) of 0.000, indicating a substantial and significant difference between the pre-test and posttest scores. This demonstrates that implementing the guided inquiry model positively impacts enhancing students' critical thinking skills.Significance- The guided inquiry learning model can be used as an alternative in teaching activities to enhance students' critical thinking skills, particularly in basic accounting materials.Keywords: Ctitical Thinking Skills; Guided Inquiry Model; Curriculum Merdeka; Democratic Learning Environment